Therapeutic Hypothermia for Neonatal Hypoxic–Ischemic Encephalopathy: Reducing Variability in Practice through a Collaborative Telemedicine Initiative - Leandro, Danieli M.K.; Variane, Gabriel F.T.; Dahlen, Alex; Pietrobom, Rafaela F.R.; de Castro, Jessica A.R.R.; Rodrigues, Daniela P.; Magalhães, Mauricio; Mimica, Marcelo J.; Van Meurs, Krisa P.; Chock, Valerie Y. (American Journal of Perinatology, 2024)
Objective This study aimed to assess the viability of implementing a tele-educational training program in neurocritical care for newborns diagnosed with hypoxic–ischemic encephalopathy (HIE) and treated with therapeutic hypothermia (TH), with the goal of reducing practice variation.Study Design Prospective study including newborns with HIE treated with TH from 12 neonatal intensive care units in Brazil conducted from February 2021 to February 2022. An educational intervention consisting of 12 biweekly, 1-hour, live videoconferences was implemented during a 6-month period in all centers. Half of the centers had the assistance of a remote neuromonitoring team. The primary outcome was the rate of deviations from TH protocol, and it was evaluated during a 3-month period before and after the intervention. Logistic regression via generalized estimating equations was performed to compare the primary and secondary outcomes. Protocol deviations were defined as practices not in compliance with the TH protocol provided. A subanalysis evaluated the differences in protocol deviations and clinical variables between centers with and without neuromonitoring.Results Sixty-six (39.5%) newborns with HIE were treated with TH during the preintervention period, 69 (41.3%) during the intervention period and 32 (19.1%) after intervention. There was not a significant reduction in protocol deviations between the pre- and postintervention periods (37.8 vs. 25%, p = 0.23); however, a decrease in the rates of missing Sarnat examinations within 6 hours after birth was seen between the preintervention (n = 5, 7.6%) and postintervention (n = 2, 6.3%) periods (adjusted odds ratio [aOR]: 0.36 [0.25–0.52], p < 0.001). Centers with remote neuromonitoring support had significantly lower rates of seizures (27.6 vs. 57.5%; aOR: 0.26 [0.12–0.55], p < 0.001) and significant less seizure medication (27.6 vs. 68.7%; aOR: 0.17 [0.07–0.4], p < 0.001).Conclusion This study shows that implementing a tele-educational program in neonatal neurocritical care is feasible and may decrease variability in the delivery of care to patients with HIE treated with TH.Key Points
Keywords: perinatal asphyxia; hypoxic–ischemic encephalopathy; therapeutic hypothermia; cooling; practice variation; educational intervention; telehealth